The problem of seeing in Feyyaz Kayacan's Short Fiction - Kaya, Nilay. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This thesis analyzes the problem of seeing in the short stories of Feyyaz Kayacan from the 1950s to the 1980s. The transformation of various forms of visual perception at social and economic levels and especially the critique of seeing's priviliged position from the beginning of modernity are dominant themes in Kayacan's short fiction. The thesis examines his multi-dimensional approach to this problem by focusing fundamentally, on the dominating nature of seeing, its potential threat to established social institutions, its role in the perception of interior and external reality and the various forrns that it can take. In addition to the formation of major themes of his short fiction through problematic of seeing, the thesis also discusses Kayacan's various surrealistic strategies to support the problem of seeing.